2014
DOI: 10.1007/s00421-014-3018-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intense physical exercise on hepcidin levels and selected parameters of iron metabolism in rowing athletes

Abstract: iron-binding capacity, unbound iron-binding capacity, iron, red blood cells, hemoglobin, hematocrit, mean corpuscular volume, creatine kinase, and myoglobin. Result The high-intensity exercise test caused significant changes in hepcidin levels, IL-6, and iron metabolism parameters, with their subsequent return to baseline values during the recovery period. The serum iron levels decreased significantly during the recovery compared with pre-and post-exercise levels. Conclusion These results suggest that the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 24 publications
5
44
1
Order By: Relevance
“…One study showed that a high-intensity exercise test caused significant changes in hepcidin levels, interleukin-6, and iron metabolism during the recovery period [11]. Another study observed that serum iron levels decreased significantly during the recovery period after exercise [23]. …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that a high-intensity exercise test caused significant changes in hepcidin levels, interleukin-6, and iron metabolism during the recovery period [11]. Another study observed that serum iron levels decreased significantly during the recovery period after exercise [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Most studies performed so far have shown that hepcidin levels return to baseline within 6 h after an acute bout of endurance exercise (Newlin et al, 2012;Sim et al, 2012;Diaz et al, 2015;Skarpanska-Stejnborn et al, 2015). However, there is a lack of data on the cumulative effects of regularly performed exercise training on the expression of iron regulatory factors and its implications for iron status and performance.…”
Section: Introductionmentioning
confidence: 99%
“…This result surprised us, because we expected that increased hepcidin would parallel the increase in IL-6, as in the study of Skarpanska-Stejnborn (33), and would reach its maximal level in acutely run rats. Skarpanska-Stejnborn et al showed a significant increase in hepcidin and IL-6 in parallel with high-intensity, shortterm exercise (33). However, some recent studies support our findings.…”
Section: Discussionmentioning
confidence: 84%